If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2t + 1) = 4(7t + 7) Reorder the terms: 8(1 + 2t) = 4(7t + 7) (1 * 8 + 2t * 8) = 4(7t + 7) (8 + 16t) = 4(7t + 7) Reorder the terms: 8 + 16t = 4(7 + 7t) 8 + 16t = (7 * 4 + 7t * 4) 8 + 16t = (28 + 28t) Solving 8 + 16t = 28 + 28t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-28t' to each side of the equation. 8 + 16t + -28t = 28 + 28t + -28t Combine like terms: 16t + -28t = -12t 8 + -12t = 28 + 28t + -28t Combine like terms: 28t + -28t = 0 8 + -12t = 28 + 0 8 + -12t = 28 Add '-8' to each side of the equation. 8 + -8 + -12t = 28 + -8 Combine like terms: 8 + -8 = 0 0 + -12t = 28 + -8 -12t = 28 + -8 Combine like terms: 28 + -8 = 20 -12t = 20 Divide each side by '-12'. t = -1.666666667 Simplifying t = -1.666666667
| 2x+4(16-x)=40 | | 0.075(x+2000)=0.08x+0.06(2000) | | X^2-36= | | .3x+.12=3.72 | | 3x-6y-2=16 | | 3t^2-48t+180=0 | | 9-26x=36 | | y-6=-25 | | 1/7(3y+2)=2+1/3(y+2) | | 3x-6y+2=16 | | 3y-6x+2=16 | | 5(x-3)=-40 | | -26-15x=19 | | 5x^2+2x-9=0 | | 2x=3x+5+865 | | -15x-26=19 | | (7z-3)(z+5)-(7z-3)(z-4)= | | 5t-2t=16 | | x*5+250=x*15-10 | | 4=18+x | | 14x+18=-10 | | 0.5(x^2+8x)= | | 4(x-5)=4x-5 | | 5x+4=3[2x-1] | | -5x-6=16 | | 4(x-5)=4x | | -8y=-6 | | 6p=-9 | | 13-9x=42-16x | | 3a-(5a+7)=20 | | -9y=-2 | | (2x+8)+(x+8)=52 |